Genetic Variability and Antibacterial Sensitivity of Dichelobacter nodosus and Fusobacterium necrophorum Infection in Sheep Sulaimani Province, Kurdistan Region, Iraq - Sulaiman, Rizgar Rahim; Marif, Hardi Fattah; Ali, Basim Abdulwahid; Ali, Kwestan Najm; Baba Shekh, Muhamad Omer (The Iraqi Journal of Veterinary Medicine, 2024)
Footrot is a significant health problem in ruminants, especially sheep, caused by the bacteria Dichelobacter nodosus and Fusobacterium necrophorum. Infected animals may become lame and lose body condition. The aim of this study was to investigate whether sheep had mixed infections with D. nodosus and F. necrophorum, the global genetic relationships of both target genes (lktA and 16S rRNA genes) with different reference genes, and the degree of genetic heterogeneity between the standard serogroups of D. nodosus were studied. In addition, to detect the antibacterial sensitivity against these two pathogens. One hundred and seventy-five sheep interdigital spaces were investigated (2016-2022). The D. nodosus field isolate (Dn Sul/016-KY399851) showed 96% compatibility with other global isolates (NR_104942/USA, JN008724/India, and DQ016290/Sweden) when its 16S rRNA sequence was compared to some reference genes. The local isolate (Fn Sul/016- KY399852) and other IktA gene strains from other nations (FJ230831/New Zealand, JX678872/Australia, JX648295/India) were compared, and the results showed 99% and 96% identity. Additionally, within the multiple sequence alignment, a single nucleotide variation at position 389 (CA) was seen in the partial lktA sequence when compared to the field isolate (Fn Sul/16-KY399852). This modification corresponds to a switch at residue 130 from alanine (Ala) to glutamic acid (Glu). This study showed the initial molecular identification of D. nodosus and F. necrophorum from sheep with footrot in the Iraqi province of Sulaimani‎‎‎‎‎.